Investigasi Visual Kelayakan Bangunan Publik di Desa Jamblang - Deni Randito Siallagan; Achmad Aprizal Ghozali; Bagus Tri Andana; Cindrawaty Lesmana; Cintiya Dewanti Santoputri; Latifah Nur Azizah; Dave Vian Nurzaqi; Mohamad Nurfian Rachmat; Krismanto Kusbiantoro; Leonardo Leonardo; Ferlina Sugata (Universitas Batanghari, 2023)
Many functional old buildings and geological condition in Indonesia are prone to disasters, hence, the investigation is needed whether those buildings are still feasible to use. Periodic inspection is one of the methods to review the buildings by standard provisions. In this study, a survey was carried out based on Permen PU No. 16/RTM/2010 and Rapid Visual Screening (FEMA P-154). Both methods were used a special form that investigates the building visually. The purpose of the study was to investigate the existing building by reviewing the damage level of building components from the structural, architectural, mechanical, and electrical aspects, as well as to seismic hazards. Based on the Minister of Public Works Regulation Number 16/RTM/2010, the results show that there are several weathered wood columns and beams, cracked walls, and many piping and electrical that are no longer functioning. Based on Rapid Visual Screening (FEMA P-154), the final value of form level 2 is 0,2 which is similar with the SMin value, which indicating that the condition of the meeting building in Jamblang Village is categorized as prone to seismic hazards, therefore, the structure strengthening is required.